Leveraging Networks to Promote Ocean Literacy - Sarah Pedemonte; Craig Strang; Chia-Dai (Ray) Yen (Current: The Journal of Marine Education)
One of the key approaches to promoting ocean literacy described by the Intergovernmental Oceanographic Commission of the United Nations during the Decade of Ocean Science for Sustainable Development is leveraging networks (UNESCO-IOC 2021). This article describes how trusted partnerships, established through cross-network collaboration within the National Marine Educators Association (NMEA) and the Asia Marine Educators Association (AMEA), are now being leveraged by the Lawrence Hall of Science, University of California, Berkeley, USA, the National Taiwan Ocean University (NTOU), the Taiwan National Academy of Marine Research (NAMR), and AMEA members from other Asian countries to share common K-12 instructional materials and implementation strategies focused on ocean literacy and climate change education.